2018
DOI: 10.1186/s12913-018-2835-1
|View full text |Cite
|
Sign up to set email alerts
|

Care relationships at stake? Home healthcare professionals’ experiences with digital medicine dispensers – a qualitative study

Abstract: BackgroundAlthough digital technologies can mitigate the burdens of home healthcare services caused by an ageing population that lives at home longer with complex health problems, research on the impacts and consequences of digitalised remote communication between patients and caregivers is lacking. The present study explores how home healthcare professionals had experienced the introduction of digital medicine dispensers and their influence on patient-caregiver relationships.MethodsThe multi-case study compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 36 publications
2
45
0
5
Order By: Relevance
“…This finding is specific to the area of health, and similarities are found when looking at the area of digital technology in health that does not use AI. A recent study by Nakrem et al 69 examined the experiences of patients and healthcare professionals using digital technology in medicine delivery. The results showed that if the healthcare professional did not understand the rationale for digital technology or believe that it would improve the relationship or the quality of care delivered, they were less likely to adopt it.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is specific to the area of health, and similarities are found when looking at the area of digital technology in health that does not use AI. A recent study by Nakrem et al 69 examined the experiences of patients and healthcare professionals using digital technology in medicine delivery. The results showed that if the healthcare professional did not understand the rationale for digital technology or believe that it would improve the relationship or the quality of care delivered, they were less likely to adopt it.…”
Section: Discussionmentioning
confidence: 99%
“…Samtidig har helsepersonellet kunnskap om pasientenes behov, og kan vurdere hvorvidt en ny tjeneste eller teknologi kan bidra til bedre helsetjeneste for den enkelte (13). De trenger imidlertid støtte fra flere hold, og dette er et større samfunnsansvar (14). Den komplekse helsetjenesten gjør at den enkelte ansatte i helsetjenesten ikke alene kan løse utfordringene (15).…”
Section: «Våre Funn Viser At Endringsviljen Hos Helsepersonellet Er Sunclassified
“…Det er derfor avgjørende at den opplaeringen som gis, tilpasses den enkelte bruker. Å introdusere velferdsteknologi på en måte som støtter pasientenes innflytelse over sin situasjon, kan redusere utfordringer ved innføring av velferdsteknologi (Nakrem, Pettersen & Kleiven, 2018). Å sikre alle ansatte nødvendig opplaering kan imidlertid vaere ressurskrevende og kostbart for mange helse-og omsorgstjenester.…”
Section: Diskusjonunclassified